2015
DOI: 10.1016/j.jbankfin.2014.05.016
|View full text |Cite
|
Sign up to set email alerts
|

Robustness of distance-to-default

Abstract: Distance-to-default (DD) is a measure of default risk derived from observed stock prices and book leverage using the structural credit risk model of Merton (1974). Despite the simplifying assumptions that underlie its derivation, DD has proven empirically to be a strong predictor of default. We use simulations to show that the empirical success of DD may well be a result of its strong robustness to model misspecifications. We consider a number of deviations from the Merton model which involve different asset v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
37
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 65 publications
(38 citation statements)
references
References 38 publications
1
37
0
Order By: Relevance
“…From Engelmann et al (2003) and Jessen and Lando (2015), our hypothesis is H 0 : AUC 1 ¼ AUC 2 for any two of our three models. The test statistic is…”
Section: Model Performancementioning
confidence: 72%
See 2 more Smart Citations
“…From Engelmann et al (2003) and Jessen and Lando (2015), our hypothesis is H 0 : AUC 1 ¼ AUC 2 for any two of our three models. The test statistic is…”
Section: Model Performancementioning
confidence: 72%
“…To compare the performance of the three models based on our sovereign balance sheet, we follow Jessen and Lando (2015) using ROC, 12 the Mann-Whitney U-test, and Spearman's q to test whether our model CDS prices can reflect the information regarding sovereign risk. Since Spearman's q is a measure of rank correlation, a high Spearman's q implies high area under the curve (AUC).…”
Section: Model Performancementioning
confidence: 99%
See 1 more Smart Citation
“…In addition to our promising results for the distance-todefault, the fact that the D2D's assumptions have been shown to be quite robust to deviations (Jessen and Lando, 2015) makes this default risk measure a very good alternative to the most commonly used market based early warning indicator. As the D2D is also available for a much broader range of banks and not only the largest ones, the D2D is also a better measure from a practical point of view.…”
Section: Introductionmentioning
confidence: 76%
“…The derivation of D2D assumes, for example, that there are no market frictions and that the fi rm's asset value follows a geometric Brownian motion, which might not be true all the time. Jessen and Lando (2015) studied the robustness of D2D on deviations from the Merton model assumptions. They found that D2D is a robust measure for ranking different fi rms according to their default risk despite deviations from most of the assumptions, except for large jumps in the asset value process or if it has stochastic volatility.…”
Section: Hypothesis 2 the Lead Of Distance-to-default On Credit Defamentioning
confidence: 99%